The Effect of Matricaria Chamomilla on Sleep Quality of Elderly People Admitted to Nursing Homes - M Abdullahzadeh; SA Naji (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Elderly people often suffer from sleep disorders. Chamomile due to its extensive health properties such as sedation could be effective in improving sleep quality in elderly people. This study aimed to determine the effect of Matricaria chamomilla extract on sleep quality in elderly people admitted to nursing homes of Isfahan in 2014.   Material & Methods: It was a quasi-experimental clinical trial. The sample consisted of 77 elderlies hospitalized in selected nursing homes of Isfahan-Iran. The sample was first recruited by convenience sampling method and then assigned to experimental and control groups. The intervention group received 400 mg oral capsules of chamomile twice daily after lunch and after dinner for 4 weeks. The control group did not receive any interventions. Sleep quality was compared before and after intervention using the Sleep Quality Questionnaire Index (PSQI). Data was analyzed by descriptive statistics and paired t and independent t tests, one way ANOVA and Liner Regression Analysis, using SPSS-PC (v.17).   Results: There was no significant difference between the mean score of sleep quality in the experimental and control group before intervention (P>0.05). A significant difference was seen after intervention between the mean score of sleep quality in experimental and control group (P<0.001). Conclusion: Oral administration of chamomile extract has sedative effects on the sleep quality of the residents of Isfahan nursing homes. Accordingly, its usage is recommended in same situations.